(untitled) (Journal of Information Technologies in Education (ITE), 2010)
The article discusses the use of innovative information technologies in modern education. Special attention is given to the using of web-multimedia technologies in the study of humanities. As an example of using information and communication tools in the process of philological disciplines described purpose, functionality and architecture of web-multimedia encyclopedia «William Shakespeare and Renaissance» (http://shakespeare.ksu.ks.ua), developed in laboratory of the integrated learning environments of the Research Institute of IT.